ELEKTRON TIJORAT VA ONLAYN SAVDONING ZAMONAVIY IQTISODIYOTDAGI OʻRNI VA RIVOJLANISH ISTIQBOLLARI (Marketing Journal, 2026)
AbstractThis article analyzes the role of e-commerce and online trade in the moderneconomy, as well as the trends and prospects for their development. The studyexamines the impact of e-commerce on entrepreneurial activity, the importance ofdigital technologies in trade processes, and the key factors influencing the developmentof online trade in Uzbekistan. The research provides a scientific justification of theeconomic efficiency of e-commerce and identifies current challenges in this field.Keywords: e-commerce, online trade, digital economy, internet technologies,electronic payment systems, entrepreneurship.